Practical approach to develop a multi‐group screening method for detection of mycotoxins, pesticides and veterinary drugs in food. (5th August 2020) - Moretti, Simone; Cavanna, Daniele; Lambertini, Francesca; Catellani, Dante; Sammarco, Giuseppe; Barola, Carolina; Paoletti, Fabiola; Saluti, Giorgio; Galarini, Roberta; Suman, Michele
Abstract: A multi‐group screening method to detect residues of veterinary drugs in meat and environmental contaminants in wheat flour has been developed using liquid chromatography coupled to quadrupole‐Orbitrap high‐resolution mass spectrometry (LC‐HRMS). The procedure was tested for over 300 representative compounds (173 veterinary drugs, 122 pesticides and 9 mycotoxins) analysing in parallel negative and positive (spiked) samples according to European validation rules. The Screening Target Concentrations (STCs) were chosen conservatively with respect to the method purposes. Interpretation of results was based on retention time, mass accuracy of precursor and MS 2 spectral library. Evaluating the percentage of false negative results, 280 out of the 304 analytes were detectable at the STCs (false compliant rate ≤ 5%). In wheat flours, incurred levels of mycotoxins, deoxynivalenol and 3‐acetyldeoxynivalenol, higher than STCs, were frequently found, whereas in meat, the most detected veterinary drugs were antibiotics generally at negligible concentrations (<10 μg kg −1 ). Finally, seven test materials from proficiency test schemes were successfully tested.